Analysis of PHBS Indicators on Double Burden Disease in Toddlers in Nii Tanasa Village, Konawe District - Yanti, Fitri; Mulyani, Sri; Rafiuddin, Ari Tjahyadi (Universitas Mandala Waluya, 2024)
Indonesia faces the challenge of a double burden of disease, where the prevalence of non-communicable diseases is increasing while communicable diseases remain high. In toddlers, this double burden includes the incidence of Acute Respiratory Infection (ARI) and nutritional problems, which are the main problems in Nii Tanasa Village, Konawe District. This study aims to analyze the relationship of Clean and Healthy Living Behavior (PHBS) indicators to the risk of double burden disease in toddlers in the region. This research design is a Cross-Sectional study with a population and sample of 43 toddlers. Data were collected through questionnaires and analyzed using the Chi-Square and Fisher Exact tests. The results of the analysis showed a significant relationship between family smoking behavior (p-value=0.015), exclusive breastfeeding (p-value=0.000), toddlers not weighed at the posyandu/health center (p-value=0.000), and main water facilities (p-value=0.000) with the incidence of double burden disease in toddlers. However, fruit and vegetable consumption did not show a significant association (p-value=0.330). This study confirms that specific PHBS indicators, such as smoking behavior, exclusive breastfeeding, and primary water facilities, are associated with the incidence of double-burden disease in toddlers. Therefore, the community needs to increase the implementation of PHBS to reduce health risks among toddlers in Nii Tanasa Village.